2016
DOI: 10.3892/ijmm.2016.2517
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and apoptosis-inducing effects of α-mangostin extracted from the pericarp of the mangosteen fruit (Garcinia mangostana L.) in YD-15 tongue mucoepidermoid carcinoma cells

Abstract: α-mangostin is a dietary xanthone which has been shown to have antioxidant, anti-allergic, antiviral, antibacterial, anti-inflammatory and anticancer effects in various types of human cancer cells. In the present study, we aimed to elucidate the molecular mechanisms responsible for the apoptosis-inducing effects of α-mangostin on YD-15 tongue mucoepidermoid carcinoma cells. The results from MTT assays revealed that cell proliferation significantly decreased in a dose-dependent manner in the cells treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…The present results are similar to those reported in the literature [13, 42] (Figure 5). Although in the coincubation scheme we did not find a significant difference between any of study groups, there is evidence in the literature indicating that α -M induces apoptosis in YD-15 tongue mucoepidermoid carcinoma cells starting at a concentration of 10  μ M [49]. …”
Section: Discussionmentioning
confidence: 63%
“…The present results are similar to those reported in the literature [13, 42] (Figure 5). Although in the coincubation scheme we did not find a significant difference between any of study groups, there is evidence in the literature indicating that α -M induces apoptosis in YD-15 tongue mucoepidermoid carcinoma cells starting at a concentration of 10  μ M [49]. …”
Section: Discussionmentioning
confidence: 63%
“…Several studies have reported that α-MG inhibited the MAPK or PI3K/Akt pathway, thereby exerting its inhibition of cell growth and induction of apoptosis in cancer cells [115]. For example, α-MG induced mitochondria-mediated apoptosis of YD-15 tongue carcinoma cells through inhibiting phosphorylation of ERK1/2 and p38 MAPK in a dose-dependent manner [23]. Phosphorylated and total ERK, JNK, and Akt were downregulated in α-MG-treated SW1353 cells, but there were no changes in p38 MAPK [88].…”
Section: Inhibition Of Survival Pathwaysmentioning
confidence: 99%
“…The proposed mechanism for α-MG-induced apoptosis was that upon α-MG treatment, the extrinsic pathway was activated, procaspase-8 was cleaved to caspase-8, and then further activated the cleavage of Bid to tBid; the tBid then translocated to mitochondria resulting in the activation of the mitochondrial apoptotic pathway [87]. The depletion of mitochondrial membrane potential, decrease in intracellular ATP, downregulation of proapoptotic Bcl-2 and upregulation of antiapoptotic Bax, release of cytochrome c from mitochondria into cytosol, activation of the caspase cascade, and enhancement of PARP cleavage were the main events involved in the mitochondrial apoptotic pathway induced by α-MG [23,88]. However, this was not in agreement with the findings of Matsumoto et al [89] who reported that α-MG directly targeted mitochondria and induced apoptosis as evidenced by the activation of caspases-9 and -3, but not caspase-8.…”
Section: Induction Of Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…The formed tBid then translocated to mitochondria leading to the stimulation of the mitochondrial apoptotic pathway [2,80]. Studies [2,81,82] have proven that depletion of mitochondrial membrane potential results in reduction in intracellular ATP, downregulation of proapoptotic Bcl-2 and upregulation of antiapoptotic Bax, secretion of cytochrome c from mitochondria into cytosol, stimulation of the caspase cascade, and augmentation of poly (ADP-ribose) polymerase (PARP) cleavage were the main events involved in the mitochondrial apoptotic pathway is triggered by α-MG. Numerous authors [83][84][85] believe that ROS is an interceder during apoptosis signaling.…”
Section: α-Mg and Apoptosismentioning
confidence: 99%